Encyclopedia of Catholic social thought, social science, and social policy - Coulter, Michael L. 1969-; Gale Group (Lanham, Maryland Scarecrow Press, 2007)
Combines theoretical work on important topics and scholarly disciplines; social science perspectives on a variety of topics; and treatment of practical policy implications that flow from applying the Catholic religious, moral, and intellectual tradition to contemporary issues.
v. 1. A-J -- v. 2. K-Z.
Electronic reproduction.
Keywords: Christian sociology -- Catholic Church -- Encyclopedias; Electronic books